Knowledge, Attitude, and Preventive Practices on Cardiovascular Diseases among the selected Community People of Gorkha (Purbanchal University Health Journal, 2025)
Background: Cardiovascular disease (CVD) is leading cause of mortality in Asian country and it is very essential to understand the current epidemiological characteristics of disease in developing countries like Nepal.Objective: The objective of the study was to assess the level of knowledge, attitude, and preventive practices regarding cardiovascular diseases among community members.Method: A descriptive cross-sectional study was conducted among 407 adults selected from the community of Gorkha using probability and multi-stage cluster random sampling techniques from May to June 2024. Data collection was conducted using the standard tool CVD-KAP29. Frequency, percentage, mean, standard deviation and chi-square was used for data analysis.Result: Majority of the respondents (77.15%) had good knowledge related to cardiovascular diseases (CVDs), and more than half (65.8%) had positive attitudes towards CVDs, 81.3% of the respondents demonstrated good practices towards CVDs. The level of knowledge was significantly associated with gender, level of education, income, and family history of CVDs. Gender, age, residence, education level, and family history of CVDs were significantly associated with attitudes. The level of practice was significantly associated with age, residence, level of education, and income.Conclusion: The study concludes that majority of the respondents had good knowledge, more than half had good attitude and majority had good preventive practices towards CVDs. While most respondents showed good knowledge and preventive practices regarding CVDs, the relatively lower proportion with a good attitude highlights the need for targeted interventions. It is recommended to strengthen health education programs to promote positive attitudes, conduct regular community-based awareness and counseling sessions, reinforce preventive practices through follow-up and support activities.